Blood loss following medial unicondylar knee replacements without a tourniquet: is there a need to group and save? - Kirmani, Sayyied J.; Middleton, Mark; Fontalis, Andreas; Srivastava, Raka; Dinah, Feroz (International Journal of Research in Orthopaedics, 2018)
Background: There are current trends towards not using a tourniquet in total knee replacement (TKR), but there is nothing published on what the effects of not using a tourniquet on unicondylar knee replacements (UKR) may be in terms of blood loss. Methods: A retrospective case series of 36 consecutive UKR from our institution were analysed. All procedures were carried out without a tourniquet and also utilised a standardised interventions protocol including withholding of anticoagulants and antiplatelet medications, administration of periarticular local anaesthetic and adrenaline injection, and both IV and topical tranexamic acid. Outcomes measured were estimated intra-operative blood loss, overall blood loss through comparison of pre and post-operative haemoglobin laboratory values, and the need for post-operative blood transfusion. Results: Most patients (61.1%) experienced an estimated intra-operative blood loss of less than100 mls. There was a mean haemoglobin drop of 16.1 g/l (range 1–26, SD ±5.9), with a mean post operatively haemoglobin level of 125.1 g/l (range 107-142, SD ±8.7). No patients required a blood transfusion. Conclusions: A low level of blood loss is encountered when UKR is undertaken without a tourniquet and with our standard interventions to reduce bleeding. The level of post-operative haemoglobin and absence of requirement for blood transfusion suggests that this operation can be undertaken without the need for a group and save. It is our hope that surgeons will be encouraged to perform this procedure without a tourniquet and benefit from the cost-saving opportunity of not performing a group and save.